Ściegi i fastrygi. Mirosław Tryczyk: Miasta śmierci. Sąsiedzkie pogromy Żydów. Warszawa, Wydawnictwo RM, 2015, ss. 499 - Kuczyńska‑Koschany, Katarzyna (Narracje o Zagładzie [czasopismo zamknięte], 2017)
Stiches and Tacks. Mirosław Tryczyk: Miasta śmierci. Sąsiedzkie pogromy Żydów. Warszawa, Wydawnictwo RM, 2015, ss. 499. The purpose of this paper, a context‑oriented presentation of Mirosław Tryczyk Miasta śmierci. Sąsiedzkie pogromy Żydów, is twofold. Firstly, it endeavours to collect and classify various responses the reviewed book has provoked: reviews, polemics, and criticism. Secondly, it proposes its own reading granting Tryczyk with the authorial right to present his own, even if diverging, type of narration. Moreover, it includes the traces of the post‑Holocaust slips of the tongue, significant and eye‑opening themselves (“And I have fled from the porch to life” [the homonym “życie” might mean both “rye” and “life,” although in different grammatical cases]). Finally, it refers to the cover and its significance, and the “excess” of death, repetitions, which deprive of hope and overwhelm the reader.